Health and nutritional status at age 0 to 6 months among some breastfed and bottle-fed infants in Metro Manila (2011)
The large decline in the number of infants being breastfed beyond 1 to 2 months of age needs clarification on what is the optimal duration for breastfeeding. Results of the 7th National Nutrition Survey show that only about one-third of children 0 to 5 months of age meet the World Health Organization (WHO) recommendation for exclusive breastfeeding. The short breastfeeding duration of 2.3 months was attributed by mothers to inadequate flow of milk. Local studies on nutritional status of breastfed or bottle-fed infants are limited. This study determined the health and nutritional status of age 0 to 6 months of 90 breastfed and 90 bottle-fed infants who were delivered in a government hospital in Metro Manila. Weight and height of infants were taken from hospital records, while information on feeding practices, recent illnesses, and reasons for breast or bottle feeding were obtained through interviews of the mothers. Mean birthweight (3010±292.85), mean birthlength (48.2±1.78 cm), and mean z-scores for weight-for-age (WAZ 0.55±0.89), length-for-age (HAZ 0.12±1.77), and weight-for-height (WHZ- 0.80±1.41) of breastfed infants were not significantly different from the mean birthweight (3005±347.74), mean birthlength (48.0±1.72 cm), and mean z-scores for weight-for-age (WAZ- 0.70±0.92), length-for-age (HAZ 0.12±1.77), and weight-for-height (WHZ- 0.72±1.89) of bottle-fed infants (ρbirthweight=0.917; ρbirthlength=0.445; ρWAZ=0.266; ρHAZ=0.376; ρWHZ=0.822). The number of illnesses due to fever, cough, and colds were higher but not significantly different between breastfed and bottle-fed infants. The number of infants with other illnesses such as allergy, diarrhea, and urinary tract infection (UTI) were reported but occurred less frequently. The most common reasons given by the mother for continued breastfeeding were the nutrition and health-giving characteristic of breastmilk, followed by the safety and hygienic aspects and the economic aspects associated with breastfeeding. Bottle-feeding was introduced within the first month of life. Among the reasons for introducing bottle-feeding were insufficient milk, cracked nipple, household chores, and employment of the mother. Additional foods were also introduced early and the reasons included the following: for additional nutrients to gain weight, it was the right age to give them, and because of insufficient milk. The most common complementary foods given were cereals, biscuits, mashed potatoes, fruit, rice, squash, and egg yolk. Most mothers introduced complementary foods at about 5 to 6 months.
Keywords: Infant nutrition